PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA PLOTAGON STORY DALAM PEMBELAJARAN MENGKREASI CERPEN PADA SISWA KELAS XI SMAN 22 BANDUNG - Amanta Fidella Mauliana; Dheni Harmaen; Adi Rustandi; Adi Rustandi (STKIP Subang, 2024)
This study was motivated by the low ability of students in writing short stories. This is due to the lack of awareness of educators in choosing the right model and learning media. The use of good learning models and media can improve the learning outcomes of learners. One of the learning models that can be used is Project Based Learning (PjBL) and Plotagon Story media in learning to create short stories in class XI students of SMAN 22 Bandung. The research method used is quasi experiment with Nonequivalent Control Group Desain. Subjects used were two classes XI SMAN 22 Bandung with each class consisting of 30 people. Data analysis techniques used are normality test, homogeneity test, and non-parametric test because the data is not normally distributed. Data testing is done using the help of SPSS 23 application to facilitates data processing. The results of the research are the average pretest experimental class of 61.33 and the value of the control class pretest of 57.66; the average value of experimental class posttest of 79.83 and the average value of the control class posttest of 67.16. The results of non-parametric statistical calculations in form of Wilcoxon signed ranks test and mann whitney-u test with Asymptotic results. Sig. (2-tailed) of 0.000 IE <0.05. So, based on these facts, it can be concluded that learning to create short stories using the model of Project Based Learning (PjBL) media-assisted Plotagon Story application on grade XI students of SMAN 22 Bandung, has been implemented and successfully.